Desarrollo de un algoritmo para el estudio de flujo de carga armónica para sistemas radiales de distribución mediante el lenguaje de programación PYTHON. - Oñate Zurita, Erik Eduardo (2020)
In this investigation an algorithm was made for the study of harmonic load flow in radial distribution systems using the Python programming language. This allowed an analysis of the penetration of non-linear loads located in different nodes of a system, with the objective of obtaining the THDi percentage respectively. In order to improve the learning and understanding of the subject, a state of the art study was carried out where the methods used in the scientific literature were analyzed, finding Newton Rapson and Gauss Seidel that are applied in meshed networks and in programs such as; Digsilent, Etap and Cymdis. Taking advantage of the topology of the distribution network, which is almost always radial, the iterative scanning method is used, which applies the first and second Kirchhoff's law together with the primitive admittance matrix for the calculation of the load flow, which allowed to obtain currents and voltages that were used for the analysis of the nodal harmonic distortion. The test results were compared with DIgSILENT, SimulAr_SR and EasyPower software demonstrating that the upstream and downstream iterative sweep method is efficient and suitable for harmonic analysis in radial distribution systems.